Examining the impact of job demand resource theory variables on burnout among hotel employees in Kuala Lumpur / Siti Nur Ellya Shahira Ahmad Nizam ... [et al.] - Ahmad Nizam, Siti Nur Ellya Shahira; Mohamad Saber, Joesri; Salim, Azlan; Zaidi, Nur Ayuni; Bahari, Khairil Anuar (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This study investigates the impact of job demand-resource theory variables on burnout among hotel employees in Kuala Lumpur, focusing on 4 and 5-star establishments. While the hospitality industry is known for its demanding work environment, this research aims to provide a comprehensive understanding of the factors contributing to burnout in this sector. Utilizing a quantitative approach and multiple linear regression analysis, data was collected through structured questionnaires distributed to food and beverages, housekeeping, and front office employees. The study highlights the significant predictors of job burnout, including workload, job resources, and personal resources, and explores how these factors influence employee well-being. One of the key findings of the study is the moderately significant influence of workload on job burnout among hotel employees. However, job resources and personal resources were identified as having a negative significant influence on burnout, suggesting the importance of providing support and development opportunities to mitigate the risk of burnout. The study also reveals that personal resources, such as self-efficacy and resilience, can act as buffers against the negative effects of workload on burnout, emphasizing the importance of fostering employee resilience in high-stress environments. Recommendations for hotel managers include addressing workload issues, providing social support, offering training and development opportunities, promoting self-care practices, enhancing feedback mechanisms, and monitoring work-life balance to prevent burnout and improve employee wellbeing. By implementing these strategies based on the study's findings, hotel managers can create a supportive work environment that prioritizes employee health and reduces the prevalence of burnout in the hospitality industry.